Isolation of actinomycetes with antibacterial activity against multi-drug resistant bacteria - Lim, Swee Siang; Selvaraj, Amsaveni; Ng, Zoe Yi; Palanisamy, Manikandan; Mickymaray, Suresh; Cheong, Peter Chiew Hing; Lim, Renee Lay Hong (Malaysian Society for Microbiology, 2018)
Aims: To isolate and characterise actinomycetes from various sources of soil samples (fruit orchard, dipterocarp forest and oil palm plantation) and to screen these isolates for antibacterial activity against multi-drug resistant bacteria. Methodology and results: A total of 158 fast-growing actinomycete isolates with different colony morphology were subjected to primary cross-streak and secondary well diffusion screening. Six isolates (OP1E, OP7A, OP2A-C, MG1A, UT9C1 and UT7E) were found to inhibit at least one of the seven multi-drug resistant (MDR) bacteria. MG1A exhibited the strongest and broadest spectrum of antibacterial activity against 6 MDR bacteria tested. These isolates were identified as Streptomyces species based on 16S rRNA gene sequence analysis. Further morphological and biochemical analysis revealed that MG1A was highly similar to S. griseocarneus (98.36%) whereas OP1E and OP2A-C were similar to S. parvulus (99.93% and 99.51% respectively). Preliminary identification using LCMS/MS and database search revealed that the major compound in the extract of OP2A-C could be dactinomycin (1255.4170 g/mol). Other antibacterial compounds in the extracts remain to be identified. Conclusion, significance and impact of study: Soil actinomycetes with antibacterial activity against MDR bacteria were isolated not only from undisturbed natural soils but cultivated soils. These isolates were characterised, identified and the antibacterial compounds were extracted for further study. The isolates could serve as a potential source for the development of new and sustainable compounds against MDR bacteria.